Keefektifan ekstra putih telur terhadap peningkatan albumin dan penurunan IL-1β pada pasien tuberkulosis dengan hipoalbuminemia - Agus Prastowo; Wiryatun Lestariana; Siti Nurdjanah; Retno Sutomo (Jurnal Gizi Klinik Indonesia, 2014)
Background: Tuberculosis (TB) is world health problem which still needs attention. Recently, Indonesia ranks the third in TB prevalence after India and China. Research revealed that albumin decreases significantly in TB patients, due to lack of nutritious intakes such as low-calorie intake, anorexia, increased catabolism, enteropathy and acute protein reaction. Low albumin was associated with increased IL-1β and cytokines inflammation in TB patient. Albumin had a very important role in the body and white egg known as a good quality source of protein.Objective: To assess the effect of white egg supplementation in TB patient towards the level of albumin and the level of IL-1β.Method: A single-blind randomized controlled trial was conducted with 75 patient selected for the study and divided to 37 patient as the study group and 38 as a control group. Both groups received high energy high protein diet, while the study group received, additionally, an oral egg white-based on formula calculation Baxter for 14 days. Control group received, additionally, an extra soybean curd and mungbean powder. Albumin and IL-1β were checked before and after the intervention. Data is analyzed by using Mann-Whitney.Results: Research results show that average albumin pre-intervention in the study group was 2.82 g/dL and control group was 2.85 g/dL. Average albumin difference in the study group was 3.47 g/dL and control group was 2.81 g/dL. Bivariate analysis results show significant of increasing albumin between study group and control group (p<0.05). Research results show average IL-1β pre-intervention difference in study group (0.9 pg/mL) and control group (0.67 pg/mL). The average IL-1β difference in the study group was -0.39 pg/mL and control group was 0.76 pg/mL. Bivariate analysis results show a significant difference of IL-1β depletion between study group and control group (p<0.05).Conclusion: Egg white increase albumin level and IL-1β depletion in tuberculosis patients effectively.